2002
DOI: 10.1109/tpami.2002.1017625
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplane approximation for template matching

Abstract: With these assumptions, ªtracking the object at time tº means ªcompute "t such that sfY "tY t sf Y " à H Y t H .º We write "t the estimate of the ground truth value " à t. The motion parameter vector of the target region "t can be estimated by minimizing the least squares function:IEEE TRANSACTIONS ON PATTERN ANALYSIS AND MACHINE INTELLIGENCE, VOL. 24, NO. 7, JULY 2002 . The authors are with LASMEAÐCNRS UMR 6602, Universite Blaise Pascal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
243
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(254 citation statements)
references
References 7 publications
4
243
0
7
Order By: Relevance
“…Randomly generated training samples are also used in the iterative procedure, e.g. Hyperplane Approximation [13], which is similar in spirit to our approach. However, they use a spatially linear distortion model along with a linear estimator (hyperplane) that does not guarantee global optimality.…”
Section: Related Workmentioning
confidence: 99%
“…Randomly generated training samples are also used in the iterative procedure, e.g. Hyperplane Approximation [13], which is similar in spirit to our approach. However, they use a spatially linear distortion model along with a linear estimator (hyperplane) that does not guarantee global optimality.…”
Section: Related Workmentioning
confidence: 99%
“…While it can be computationally expensive, [50] showed that under some conditions, it can be effectively formulated. Since then it has been extended by several authors and applied to 3D tracking [19,65,66].…”
Section: Template Matchingmentioning
confidence: 99%
“…The approach presented in [66] relies on a reinterpretation of Equation (4.13) that yields a faster implementation than the Jacobian formulation discussed above. It treats the equation as an approximation by hyperplanes.…”
Section: Hyperplane Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tracking algorithms still suffer from fundamental problems including drifts away from targets [4] (partially due to change of viewpoint), inability to adapt to changes of object appearance, dependence on the first frame for template matching [5], instability to track objects under deformations (e.g. deformed contours), the inefficiency of Monte Carlo simulations for temporal tracking [6], and reliance on gradients by active contours [7], i.e.…”
Section: Introductionmentioning
confidence: 99%